Activation of invariant natural killer T cells in regional lymph nodes as new antigen‐specific immunotherapy via induction of interleukin‐21 and interferon‐γ. (October 2014) - Sakurai, T.; Inamine, A.; Iinuma, T.; Funakoshi, U.; Yonekura, S.; Sakurai, D.; Hanazawa, T.; Nakayama, T.; Ishii, Y.; Okamoto, Y.
Summary Invariant natural killer T (iNKT) cells play important immunoregulatory functions in allergen‐induced airway hyperresponsiveness and inflammation. To clarify the role of iNKT cells in allergic rhinitis (AR), we generated bone marrow‐derived dendritic cells (BMDCs), which were pulsed by ovalbumin (OVA) and α‐galactosylceramide (OVA/α‐GalCer‐BMDCs) and administered into the oral submucosa of OVA‐sensitized mice before nasal challenge. Nasal symptoms, level of OVA‐specific immunoglobulin (IgE), and T helper type 2 (Th2) cytokine production in cervical lymph nodes (CLNs) were significantly ameliorated in wild‐type (WT) mice treated with OVA/α‐GalCer‐BMDCs, but not in WT mice treated with OVA‐BMDCs. These anti‐allergic effects were not observed in Jα18–/– recipients that lack iNKT cells, even after similar treatment with OVA/α‐GalCer‐BMDCs in an adoptive transfer study with CD4+ T cells and B cells from OVA‐sensitized WT mice. In WT recipients of OVA/α‐GalCer‐BMDCs, the number of interleukin (IL)‐21‐producing iNKT cells increased significantly and the Th1/Th2 balance shifted towards the Th1 dominant state. Treatment with anti‐IL‐21 and anti‐interferon (IFN)‐γ antibodies abrogated these anti‐allergic effects in mice treated with α‐GalCer/OVA‐BMDCs. These results suggest that activation of iNKT cells in regional lymph nodes induces anti‐allergic effects through production of IL‐21 or IFN‐γ, and that these effects are enhanced by simultaneous stimulation with antigen. Thus, iNKT cells might be a useful target in development of new treatment strategies for AR.